Bibliometrične študije statističnih metod na področju biomedicine kot podpora načrtovanju pedagoškega procesa - Vidmar, Gaj (Zdravstveno varstvo, 2003)
Several courses in biostatistics are taught at the Institute of Biomedical Informatics of the University of Ljubljana as part of undergraduate and graduate study at the Faculty of Medicine, undergraduate study at the School of Public Health and in collaboration with the Institute of Public Health. Thetopics covered range from fundamentals to multivariate methods, and course objectives and contents are constantly adjusted to students' profile. One of our efforts aimed at keeping the curriculum up-to-date and ensuring quality ofeducation is a regular bibliometric research. Two surveys of statistical methods applied in scientific papers were carried out: one in the New England Journal of Medicine and one in four journals from the field of public health, accessible in full-text electronic form from our university. For this purpose,a taxonomy of statistical methods based on consulting practice was designed. A summary of findings is presented, including data presentation issues and software usage. Implications are discussed focusing on our graduatecourse in contemporary statistical methods in medicine. Possible topics for courses and summer schools in data analysis in public health are proposed. Bibliometric analyses are demanding and call for a combination of quantitative and qualitative methods, but if carried out correctly, they can markedly improve the quality of education via curriculum development. At our institute, we will continue to follow new developments in statistics through bibliometric studies.
Keywords: biomedicina; biostatistika; javno zdravje; statistične metode; statistika